PENGARUH GAYA KEPEMIMPINAN KASAT SABHARA SIAK TERHADAP DISIPLIN KERJA ANGGOTA SABHARA SIAK DI POLRES SIAK KECAMATAN DAYUN - Ariyani, Fitri; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Kecamatan Dayun. The purpose of this research is to know knowing forms of Siat Siak polite leadership style at Kecamatan Dayun. The focus of this research is the influence of leadership style on discipline level of Sabhara members in Police at Kecamatan Dayun. Sampling technique in this research is Census Method which means all population will be Respondent. and set a total sample of 47 people. The author uses quantitative methods and Instruments data is observation, questionnaires and documentation. The study found that Respondents of Sabak Village Sabhara Respondents respond to autocratic leadership is firmly (51.1%) but with the form of invisible authoritarian leadership style in the current period because the leader of Sabhrara is currently firm but not to cause the element of coercion and excessive pressure to members when doing duty service. Members of sabhara respond to democratic leadership, leaders have an open nature (80.9%) with democratic democratic leadership. Members of sabhara respond to permissive leadership in fixed position (53.2%) with permissive leadership because according to the respondent is not unlike someone who is not fixed its establishment. The contribution of variable use of leadership style to the level of discipline obtained is 66% with 60% coefficient interval - 79.99% level categories have a strong effect. That is, a significant influence between Sabhara Siak's Leadership Style on Sabhara Member Working Discipline in Siak District Police Dayun Sub-district is influenced by 66% with strong influence category. Keywords: Leadership, Discipline, Social Action